Étude Évaluative De L'application Des Textes Juridiques En Vigueur En Matière De Lutte Contre La Contrefaçon En Côte d’Ivoire - Sylvère, Kazon Diescieu Aubin; Stéphane, Dagbé Ahodan; Edwige, Blé (European Scientific Journal, ESJ, 2018)
This study aim at assessing the application of laws within the fight against counterfeiting in Ivory Coast. The work took place in Abidjan (the economic capital city), precisely in the communes of Plateau and Koumassi and has focused on a sample of 32 respondents selected according to the criteria of intentional sampling method. The data have been collected by direct observation and with the help of a questionnaire; all from the documentary study. As far as the methods of analysis of the data are concerned, the emphasis has been placed on the qualitative analysis. Thus, the results obtained show many difficulties in the application of the legal texts in the field of the fight against counterfeiting. These difficulties result in large part from the legal problems and the enforcement of decisions, the lapsing of certain laws which are more in line with the requirements of international trade and of the inadequacy of some laws. From these results, we propose that the sentences are more dissuasive and the fines very high. The means must be put at the disposal of sworn officers to rigorously enforce the laws. They will need to have coercive powers, or even law enforcement agencies to track down counterfeiters and spurious goods. There must be an honest collaboration between economic operators and agents in charge of making the laws respected.